2014
DOI: 10.1158/1541-7786.mcr-13-0458
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 Mediates TWEAK/Fn14-Induced Non–Small Cell Lung Cancer Survival and Therapeutic Response

Abstract: Insensitivity to standard clinical interventions, including chemotherapy, radiotherapy and tyrosine kinase inhibitor (TKI) treatment, remains a substantial hindrance towards improving the prognosis of patients with non-small cell lung cancer (NSCLC). The molecular mechanism of therapeutic resistance remains poorly understood. The TNF-like weak inducer of apoptosis (TWEAK)-FGF-inducible 14 (Fn14) signaling axis is known to promote cancer cell survival via NF-κB activation and the up-regulation of pro-survival B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 44 publications
1
32
0
1
Order By: Relevance
“…NF-kB activity induced by miR-29b leads to upregulation of antiapoptotic genes, rendering cancer cells insensitive to the extrinsic apoptotic program (39). Expression of BCL2 family members is also induced by NF-kB conferring insensitivity to cisplatin (40). However, it is well established that miR-29b directly targets the antiapoptotic gene MCL1 in lung cancer (41), tipping the balance toward intrinsic apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB activity induced by miR-29b leads to upregulation of antiapoptotic genes, rendering cancer cells insensitive to the extrinsic apoptotic program (39). Expression of BCL2 family members is also induced by NF-kB conferring insensitivity to cisplatin (40). However, it is well established that miR-29b directly targets the antiapoptotic gene MCL1 in lung cancer (41), tipping the balance toward intrinsic apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al, 2017;C. T. Lee et al, 2003;Liu et al, 2007;Luo et al, 2016;Okamura et al, 2012;Qian et al, 2014;Shin, Choi, & Park, 2014;Whitsett et al, 2014;D. W. Wu et al, 2014;Xiao et al, 2017).…”
Section: Discussionunclassified
“…22 Inhibition of Mcl-1 function enhanced chemo-and radio-sensitivity in NSCLC cells. 23 A clinical study detected Mcl-1 protein expression in NSCLC, Mcl-1 was expressed in 38.1% of squamous cell carcinoma and 45.8% of lung adenocarcinoma, but no significant differences of Mcl-1 expression were detected between the two main types of NSCLC. Overexpression of Mcl-1 was significantly associated with high pathological grade (P ¼ 0.022) and lymph node involvement (P ¼ 0.017) and also correlated with poor prognosis of the patient studied.…”
Section: Prognostic Significance Of Anti-apoptotic Bcl-2 Family Protementioning
confidence: 96%
“…The great majority of the reported studies on Mcl‐1 have been in vitro studies and Mcl‐1 has been reported to be critical for the survival of NSCLC cell lines and stem‐like cells in NSCLC showed higher Mcl‐1 expression . Inhibition of Mcl‐1 function enhanced chemo‐ and radio‐sensitivity in NSCLC cells . A clinical study detected Mcl‐1 protein expression in NSCLC, Mcl‐1 was expressed in 38.1% of squamous cell carcinoma and 45.8% of lung adenocarcinoma, but no significant differences of Mcl‐1 expression were detected between the two main types of NSCLC.…”
Section: Antibodies Used For Immunohistochemistrymentioning
confidence: 99%